Enhancing PhD Education: Research Collaboration and Assistantship Insights from Columbia Teachers College and Georgian Universities - Irma Machitidze; Irina Bakhtadze (European Scientific Journal, ESJ, 2025)
Postgraduate education has always been a vital component of academic development, delivering specific expertise and knowledge and advancing innovation throughout different sectors of science and industry. In the context of an ever-changing environment, universities seek to improve their postgraduate programs by embracing successful models from different parts of the world. This endeavor of improvement necessitates an integrated approach to forward-looking postgraduate studies, designed to equip learners with the knowledge and competencies needed to thrive not only in conventional scholarly careers but also in a broader spectrum of positions within non-academic circles. All earnest efforts should be made to nurture the competencies of doctoral students to become applicable for diverse fields, such as industry, public or private sectors, non-profit institutions, and business organizations, therefore facilitating graduates to find their way in a competitive labour market successfully. The focus of this paper is to identify and analyze the advantages associated with experiential teaching and learning through professor assistantships and cooperative research in doctoral programs. This paper uses qualitative data and analyzes them from institutional policy documents and primary documents such as curriculum and policies for teaching/learning in postgraduate courses at Columbia Teachers College, NYU, and recent changes to institutional regulations concerning doctoral education at International Black Sea University (IBSU). Additionally, it investigates specific mechanisms embedded in these programs that foster development at both the prospective academic and professional levels. The findings suggest that professor assistantships and collaborative research are considered valuable experiences that benefit both doctoral students and the staff of the university through the development of teaching experience, professional development, and mentor/mentee relationships. Finally, this paper gives insight and recommendations for Georgian universities based on successful models found and could have implications for the quality and relevance of doctoral programs and their ability to prepare graduates for the competitive and diverse labour markets.